Peptide Antigen Modifications Influence the On-Target and Off-Target Antibody Response for an Influenza Subunit Vaccine - Megan C. Schulte; Adam C. Boll; Agustin T. Barcellona; Elida A. Lopez; Adam G. Schrum; Bret D. Ulery (Vaccines)
Background/Objectives: Peptide amphiphile micelles (PAMs) are an exciting nanotechnology currently being studied for a variety of biomedical applications, especially for drug delivery. Specifically, PAMs can enhance in vivo trafficking, cell-targeting, and cell interactions/internalization. However, modifying peptides, as is commonly performed to induce micellization, can influence their bioactivity. In our previous work, murine antibody responses to PAMs containing the influenza antigen M22–16 were slightly incongruous with prior PAM vaccine studies using other antigens. In this current work, the effect of native protein linkages and non-native micellizing moieties on M2 immunogenicity was studied. Methods: PAMs were synthesized using an elongated M2 antigen (i.e., Palm2K-M21–24-(KE)4). The PAMs were characterized, then their immunogenicity was evaluated with bone marrow-derived dendritic cells and in mice. Results: Although the modification scheme yielded immunogenic PAMs, these PAMs induced a substantial amount of off-target antibody production compared to unmodified peptidyl micelles (PMs, M21–24 peptide). Conclusions: While the impact PAM-induced off-target antibodies had on vaccine efficacy remains to be elucidated, on-target antibodies from both PAM- and PM-vaccinated mice were excitingly able to recognize the M2 antigen within the context of the full M2 protein. This provides preliminary evidence that the PAM-induced on-target antibodies will at minimum be able to recognize the influenza virus upon exposure.